2014
DOI: 10.1007/s11999-013-3439-z
|View full text |Cite
|
Sign up to set email alerts
|

Relative Fixation Strength of Rabbit Subscapularis Repair Is Comparable to Human Supraspinatus Repair at Time 0

Abstract: Background Recent evidence suggests that the rabbit subscapularis tendon may be anatomically, biomechanically, and histologically suitable to study rotator cuff pathology and repair. However, biomechanical comparisons of rotator cuff repairs in this model have not been evaluated and compared to those in human cadaveric specimens. Questions/purposes We quantified the biomechanical properties of the repaired rabbit subscapularis tendon after (1) single-row, (2) double-row, and (3) transosseousequivalent rotator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Thus, rabbits were considered a suitable animal model to research rotator cuff pathology, especially that caused by extrinsic factor alterations (e.g., biomechanical changes) 22 . In recent years, rabbit models have been extensively applied in rotator cuff repair research 23 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rabbits were considered a suitable animal model to research rotator cuff pathology, especially that caused by extrinsic factor alterations (e.g., biomechanical changes) 22 . In recent years, rabbit models have been extensively applied in rotator cuff repair research 23 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rat model developed by Soslowsky et al [6] is considered as the most suitable rotator cuff model due to its similarity to human anatomy (the presence of an acromial arch) and its range of motion [5]. The determination of the most suitable animal rotator cuff model allows for in vivo simulation to analyze different factors affecting the repair process, thus improving the therapeutic process [7]. Several studies dealing with tissue reconstruction via suture patterns or scaffolds used animal specimens to perform tests, especially horse [8], dog [9], and swine [10] tendons.…”
Section: Introductionmentioning
confidence: 99%
“…(3) transosseous-equivalent RC repair techniques, and found that the initial biomechanical characteristics of these repairs were similar to human SSP RC repairs performed in cadaveric specimens 12 . As such, the anatomical, physiological, and biomechanical similarity of rabbit SSC with human SSP makes it useful for modeling RC injuries.…”
Section: Otarodifard Et Al Assessed the Biomechanical Characteristicsmentioning
confidence: 86%